Efficient Class-E design for inductive powering wireless biotelemetry applications - Saad Mutashar, Abbas; M. A., Hannan, Dr.; Salina, Abdul Samad, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/